Indian Freedom Struggle: The Pathfinders From Surendranath Banerjea - B Krishna; KRISHNA (B) (New Delhi Manohar Publishers, 2002)
The Indian Freedom Struggle Has Been Covered From 1876 To 1947, Not From 1885 When The Indian National Congress Was Established. Because That Year Surendranath Banerjea Had Laid The Foundations Of The Freedom Movement.
Keywords: Indian History; Freedom Fighters